Meningkatkan Daya Saing Pasar UMKM Melalui Transformasi Digital - Ustadus Sholihin (Universitas 45 Surabaya, 2024)
Digital transformation has become an important key in increasing the market competitiveness of Micro, Small and Medium Enterprises (MSMEs). In this research, various important aspects related to the digitalization of MSMEs are discussed, including the role of social communities in contributing ideas and finding solutions to digitalization problems, as well as collaboration between the government, educational institutions and related agencies in supporting the growth of MSMEs. This research also highlights the difficulties, variables and methodologies in running a web-based business, as well as the importance of data innovation in increasing market efficiency. Focusing on fish marketing, research also shows that the use of information and communications technology (ICT) can influence market efficiency. The results of this research provide recommendations for developing curriculum and development programs that can support MSMEs in facing the challenges of digitalization and increasing the competitiveness of small businesses.